2013
DOI: 10.1111/joms.12004
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Pathways of Change in Professional Services Firms: The Case of Management Consulting

Abstract: This paper contributes to the debate about new organizational forms in professional service firms (PSFs) by suggesting an alternative to extant accounts of how change takes place. To explain the displacement of community forms of organizing by more corporate forms, much of the literature has so far focused on intra‐archetype adaptation and evolutionary processes, looking mainly at established PSFs in law and accounting. Drawing on ideas from the sociology of professions and institutional theory, we suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 89 publications
(160 reference statements)
3
54
0
1
Order By: Relevance
“…Adler & Kwon, 2013;Muzio, Brock & Suddaby, 2013;Bevort & Suddaby, 2016). Following on from the work of Scott (2008) and more recent contributions by Muzio, Brock & Suddaby, (2013), Adler & Kwon, (2013), Kipping & Kirkpatrick, (2013) we emphasized the value of studying professions as institutions, and connected the patterns of professionalization with the broader processes of institutionalization. So how does our analysis of institutional maintenance help us explain maintenance of professions?…”
Section: Maintenance Of Closure and Reproduction Of The Status Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…Adler & Kwon, 2013;Muzio, Brock & Suddaby, 2013;Bevort & Suddaby, 2016). Following on from the work of Scott (2008) and more recent contributions by Muzio, Brock & Suddaby, (2013), Adler & Kwon, (2013), Kipping & Kirkpatrick, (2013) we emphasized the value of studying professions as institutions, and connected the patterns of professionalization with the broader processes of institutionalization. So how does our analysis of institutional maintenance help us explain maintenance of professions?…”
Section: Maintenance Of Closure and Reproduction Of The Status Ordermentioning
confidence: 99%
“…Muzio, Brock & Suddaby (2013) emphasized the value of studying professions as institutions, and connected the patterns of professionalization with the broader processes of institutionalization. Viewed from this perspective, professions are not only the key mechanisms for institutional change, but also the primary targets of the processes of institutionalization (Greenwood, Suddaby & Hinings, 2002;Reay & Hinings, 2009;Suddaby & Viale, 2011;Adler & Kwon, 2013;Kipping & Kirkpatrick, 2013). We refer to advocates as an institution and, because all Scottish advocates belong to the Faculty of Advocates, we treat the Faculty as the organizational aspect of the institution following a long-standing recognition of both normative and structural elements of institutions (Scott, 1987;Gutierrez, Howard-Grenville & Scully, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing these studies, we found that fields often form and change around opportunities, such as the pursuit of a promising new technology (cochlear implants in Garud, 2008;photography in Munir & Phillips, 2005; and nanotechnology in Meyer, Gaba & Colwell, 2005), a new market or area of practice (e.g., consulting in Kipping & Kirkpatrick, 2013; information schools in Patvardhan et al, 2015), or to take advantage of a regulatory shift (Purdy & Gray, 2009). A less elaborated institutional infrastructure, or one that is fragmented, provides space for innovation and also weaker points in field boundaries, enabling entry of new actors.…”
Section: Triggers For Changementioning
confidence: 99%
“…The changing nature of PSFs is driven by institutional forces such as industry regulations, technological developments, and increased globalization (Brock and Powell 2005;Brock 2006;Brock 2012;Greenwood and Empson 2003;Kipping and Kirkpatrick 2013) which offer new opportunities for search and learning processes in IPSFs. For instance, by pursuing a transnational strategy, IPSFs get opportunities for global knowledge sourcing, and technological innovations through providing globally integrated services (Breunig et al 2014;Muzio and Faulconbridge 2013;Segal-Horn and Dean 2011).…”
Section: The Nature Of Innovation In Ipsfsmentioning
confidence: 99%